Corporate social responsibility practices and enterprise risk management of the GCC Islamic banks - Alsalami, Tamader; Low, Soo-Wah; Nor, Shifa Mohd; Alsheikh, Awatif Hodaed (International Journal of Management and Sustainability, 2023)
This study intends to investigate the impact of CSR practices on ERM implementation, focusing on Islamic banks operating in Gulf Cooperation Council (GCC) countries. Following the banking industry’s collapse during the 2008 financial crisis, there has been a notable rise in the enactment and literature of Corporate Social Responsibility (CSR). Although the influence of CSR practices on performance, trust, and reputation has been extensively researched, limited research studies have examined their impact on enterprise risk management (ERM). The study uses secondary data obtained from the annual reports of 23 Islamic banks between 2011 and 2020. CSR practices and ERM implementations were scored using content analysis. Using panel regression techniques, we find a significant positive relationship between CSR practices and ERM implementation for listed Islamic banks over the sample period. The relationship remains intact across two distinct ERM measures and various estimation methods. The findings of the study contribute to the literature by offering valuable empirical evidence of the effect of corporate social responsibility practices on enterprise risk management implementation in the GCC Islamic banks. The study suggests that executives, policymakers, and regulators of Islamic banks in the GCC should support and endorse socially related initiatives to aid in the successful implementation of ERM.